Numerical modelling and experimental validation of the effect of laser beam defocusing on process optimization during fiber laser welding of automotive press-hardened steels. (July 2021) - Shehryar Khan, M.; Shahabad, S.I.; Yavuz, M.; Duley, W.W.; Biro, E.; Zhou, Y.
Graphical abstract: Highlights: This work uses numerical modelling and experimental validation to study the effect of laser beam defocusing on the weld pool geomtery during the laser welding of 22MnB5 grade press-hardened steel. The study presents the effect of beam defocusing on the weld pool geometry while holding other parameters constant, as the welding mode transitions from the full penetration mode when the beam is fully focused, to the partial penetration mode as the beam is defocused. It has been shown through a detailed experimental study that by defocusing the laser beam, the welding process can be stabilized which allows the weld pool geometry to be controlled and leads to the elimination of defects such as severe concavity without needing to decrease the laser power or welding speed. A numerical solution is presented that uses three-dimensional transient finite element analysis to calculate the temperature fields and predict the molten weld pool geometry in both the full and partial penetration welding modes to show how the change in beam defocusing distance impacts the shape and size of the weld. The findings of this work have a high impact potential as the simple, yet highly accurate numerical model presented in this work allows for the proposed method of defocusing the laser beam to improve the stability of the laser welding process, so it can be readily used in streamlining the manufacturing of laser-welded blanks used in the automotive industry. Abstract: Automated robotic laser welding is commonly used for the joining of thin-gauge sheet metals for automotive applications due to the precision and speed of the welding process. Without proper process optimization, high-speed laser welding for automotive applications is known to have defects such as porosity, weld concavity, and cyclic humping. Several welding parameters can be adjusted to optimize the laser welding process: decreasing the laser power and the welding speed, changing the intensity distribution of the laser on the surface of the substrate, or by changing the type and flow rate of shielding gas used during welding. However, decreasing the laser power and welding speed leads to a loss in productivity which can be costly in large-scale manufacturing endeavors. This study presents the effect of beam defocusing on the weld pool geometry while holding other parameters constant as the welding mode transitions from full penetration or open keyhole mode (OKM) when the beam is fully focused to partial penetration or closed keyhole mode (CKM) as the beam is defocused. It has been shown that by defocusing the laser beam and controlling the weld pool geometry, the welding process can be stabilized to eliminate defects such as severe concavity without decreasing the laser power or slowing down the welding process. A numerical solution is presented that uses three-dimensional (3D) transient finite element (FE) analysis to calculate the temperature fields and predict the molten weld pool geometry in both the full and partial penetration welding modes using a double conical-Gaussian (DCG) volumetric heat source derived from the classical 3D conical-Gaussian (CG) heat source. The model was calibrated using video imaging of the welding process and known experimental data, and it was validated using an extensive experimental study. The results of this work show that the model can be used to predict the molten weld pool geometry that stabilizes the liquid flow in the melt pool during high-speed laser welding whereby allowing faster speeds to be used in the manufacturing of laser-welded components.